2015
DOI: 10.5194/bgd-12-12899-2015
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Stable isotope study of a new chondrichthyan fauna (Kimmeridgian, Porrentruy, Swiss Jura): an unusual freshwater-influenced isotopic composition for the hybodont shark <i>Asteracanthus</i>

Abstract: Abstract. Chondrichthyan teeth (sharks, rays and chimaeras) are mineralised in isotopic equilibrium with the surrounding water, and parameters such as water temperature and salinity can be inferred from the oxygen isotopic composition (δ18Op) of their bioapatite. We analysed a new chondrichthyan assemblage, as well as teeth from bony fish (Pycnodontiformes). All specimens are from Kimmeridgian coastal marine deposits of the Swiss Jura (vicinity of Porrentruy, Ajoie district, NW Switzerland). While the overall … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…In previous studies δ 18 O PO4 from enameloid and dentine showed no significant differences for the given setting [ 29 , 37 ]. Moreover, bulk sampling is commonly employed when only small teeth or not enough samples are available [ 33 35 , 86 ]. In the case of batoids, most of the sampled material consists of dentine.…”
Section: Methodsmentioning
confidence: 99%
“…In previous studies δ 18 O PO4 from enameloid and dentine showed no significant differences for the given setting [ 29 , 37 ]. Moreover, bulk sampling is commonly employed when only small teeth or not enough samples are available [ 33 35 , 86 ]. In the case of batoids, most of the sampled material consists of dentine.…”
Section: Methodsmentioning
confidence: 99%
“…). Euryhaline character of the hybodont Asteracanthus , recently demonstrated through stable isotope analyses, so far only in the study area (Leuzinger et al . ).…”
Section: Water Salinitymentioning
confidence: 97%
“…Leuzinger et al . () demonstrated with stable isotope analyses that this genus tolerated reduced salinity, broadening the range of potential ecological niches and prey items.…”
Section: Palaeoecologymentioning
confidence: 99%
“…During the Kimmeridgian, the climate of the Jura carbonate platform was semi-arid subtropical to Mediterranean with strong seasonal differences between prolonged, warm, dry summers and relatively short, wet winters, e.g., [3944]. The presence of freshwater on the platform is corroborated by the occurrence of charophytes [45,46] and hybodontid shark teeth that display an unusual freshwater isotopic signal [47]. …”
Section: General Settingmentioning
confidence: 99%